2021
DOI: 10.3389/fimmu.2021.729209
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Lactate Acts as a Metabolic Checkpoint and Shapes Monocyte Function Time Dependently

Abstract: Elevated blood lactate levels are frequently found in critically ill patients and thought to result from tissue hypoperfusion and cellular oxygen shortage. Considering the close relationship between immune cell function and intracellular metabolism, lactate is more than a glycolytic waste molecule but able to regulate the immune response. Our aim was to elucidate the temporal and mechanistic effect of extracellular lactate on monocytes. To this end, primary human monocytes and the human monocytic cell line Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Lactate is a major end product of glycolysis and is emerging as a regulator of metabolism with complex, cell type-specific effects ( 56 58 ). Similar to pyruvate, lactate can be used for gluconeogenesis, but its major established role is as a signaling intermediate that functions inside and between cells to alter function and activation state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate is a major end product of glycolysis and is emerging as a regulator of metabolism with complex, cell type-specific effects ( 56 58 ). Similar to pyruvate, lactate can be used for gluconeogenesis, but its major established role is as a signaling intermediate that functions inside and between cells to alter function and activation state.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to pyruvate, lactate can be used for gluconeogenesis, but its major established role is as a signaling intermediate that functions inside and between cells to alter function and activation state. For example, in monocytes, macrophages and T lymphocytes, elevated levels of lactate inhibit glycolysis and have been linked to immunosuppression as indicated by impaired production of proinflammatory cytokines by monocytes, changes in macrophage gene expression leading to M2 polarization, and impaired CD8+ T cell proliferation and toxicity ( 57 , 58 ). In contrast, lactate signaling in tumor cells increases glucose uptake, enhances expression and activity of glycolysis enzymes and reduces mitochondrial function via a mechanisms linked to HIF-1α and PIK3CA ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sorbitol, fructose, and NADH are the overall products of the polyol pathway [ 56 ]. Sorbitol accumulates in primary human monocytes and the human monocytic cell line, MonoMac6, by the stimulation of exogenous lactate [ 57 ]. In our study, sorbitol was undetected in our NMR spectra due to its low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…63 Yang et al demonstrated a new mechanism by which lactate plays a previously unknown role in inhibiting proinflammatory cytokine production via GPR81-mediated Yes-associated protein (YAP) inactivation, leading to the interruption of YAP and NF-κB interactions and nuclear translocation in macrophages. 64 Schenz et al 65 suggested that extracellular lactate acts as a metabolic checkpoint independent of the already-known GPR81 signaling-dependent mechanism and shapes monocyte function via distinct acute and long-term effects. Temporary elevation of systemic lactate may be considered a mechanism to withstand excessive inflammation.…”
Section: Metabolic Regulation In Immunosuppressionmentioning
confidence: 99%